Oculoplastics and Orbit Aesthetic and Functional Oculofacial Plastic Problem-Solving in the 21st Century - Guthoff, Rudolf F.; Katowitz, James A.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
The third volume of Oculoplastic and Orbital Surgery continues in the excellent tradition of this unique series. The new volume offers readers a comprehensive update on a number of complex and challenging orbital disorders, including idiopathic orbital inflammation, ocular adnexal lymphoproliferative disorders, metastatic orbital tumors, and the latest therapies in the management of capillary hemangiomas, periorbital infections, and orbital and periorbital malignancies using specific targeted therapies. Modern concepts in orbital imaging are also highlighted, as are controversies in enucleation techniques with suggestions regarding the most effective ocular implants. Management of complex eyelid and periorbital problems is presented. This includes chapters on managing orbitofacial neurofibromatosis 1 and brow suspension for complicated unilateral ptosis. In addition, systemic and ophthalmic anomalies in congenital anophthalmos and microphthalmos are comprehensively reviewed. Lacrimal disorders, including the diagnosis and management of canalicular obstruction and lesions of the lacrimal drainage system encountered with dacryocystorhinostomy, are also presented. The area of cosmetic surgery is thoroughly covered in an extensive chapter discussing pearls in cosmetic oculofacial plastic surgery and another chapter presenting the latest concepts in using fillers for volume enhancement in the orbit and periorbit. As with the previous two volumes, the presentation of the latest concepts and management techniques in the field of oculofacial plastic surgery will prove to be an invaluable resource for both the comprehensive ophthalmologist and the subspecialist with a particular interest in disorders of the orbit, eyelids, and lacrimal system.
Ocular Adnexal Lymphoproliferative Disease -- Pearls in Cosmetic Oculofacial Plastic Surgery -- Current Concepts in the Management of Idiopathic Orbital Inflammation -- Lacrimal Canalicular Inflammation and Occlusion: Diagnosis and Management -- Orbitofacial Neurofibromatosis 1: Current Medical and Surgical Management -- Clinicopathologic Features of Lesions Affecting the Lacrimal Drainage System in External Dacryocystorhinostomy -- Systemic and Ophthalmic Anomalies in Congenital Anophthalmic or Microphthalmic Patients -- Brow Suspension in Complicated Unilateral Ptosis: Frontalis Muscle Stimulation via Contralateral Levator Recession -- Modern Concepts in Orbital Imaging -- Management of Periorbital Cellulitis in the 21st Century -- Current Concepts in the Management of Infantile Hemangiomas: Steroids, Beta-Blockers, or Surgery -- Evaluation and Management of Metastatic Orbital Tumors -- Targeted Therapy in the Treatment of Orbital and Periorbital Malignancies -- Controversies in Enucleation Technique and Implant Selection: Whether to Wrap, Attach Muscles, and Peg? -- Non-surgical Volume Enhancement with Fillers in the Orbit and Periorbital Tissues: Cosmetic and Functional Considerations.
Keywords: Medicine; Ophthalmology; Surgery; Medicine & Public Health; Ophthalmology; Oral and Maxillofacial Surgery